POSTOPERATIVE CARE AND PREVENTION OF COMPLICATIONS (International journal of medical sciences, 2025)
Postoperative care is a critical component of surgical practice, designed to optimize recovery, reduce complications, and improve patient outcomes. It involves continuous monitoring, pain management, infection prevention, nutritional support, and psychological rehabilitation. Effective postoperative care requires a multidisciplinary approach involving surgeons, anesthesiologists, nurses, physiotherapists, and nutritionists. Despite advances in surgical techniques, postoperative complications remain a significant cause of morbidity and mortality. Common complications include wound infection, pneumonia, thromboembolism, cardiovascular events, and delayed wound healing. Preventive strategies such as early mobilization, prophylactic antibiotics, venous thromboembolism (VTE) prevention, and enhanced recovery after surgery (ERAS) protocols are widely used to minimize risks. Moreover, patient education, careful monitoring of vital signs, and timely intervention in the event of deterioration are crucial for safe recovery. This article reviews modern postoperative care principles and strategies for preventing complications, with an emphasis on evidence-based approaches. By integrating clinical monitoring with preventive strategies, healthcare professionals can significantly enhance surgical outcomes and ensure better quality of life for patients after surgery.